Does microcycle length influence the external and internal load in professional female soccer players? - Manuel Posse-Álvarez; David Solleiro-Duran; Miguel Lorenzo-Martínez; Eliseo Iglesias-Soler; José M. Oliva-Lozano; Alexis Padrón-Cabo (Biology of Sport)
This study aimed to analyze the effects of microcycle length on external and internal load during training sessions and official matches in a professional female soccer team. A total of 32 microcycles were monitored for 20 outfield players using a portable 10 Hz GPS device. Microcycles were categorized by length as short (5–6 days), regular (7 days), or long (8–9 days). Training load during the microcycles was analyzedrelative to the days before or after the match day (MD), considering the following sessions: MD+1, MD-4, MD-3, MD-2, and MD-1. The external load was assessed according to total distance (TD), high-intensity running distance (HIR), sprint distance (SPD), and number of high-intensity accelerations (ACC) and decelerations (DEC). Internal load was measured using the rating of perceived exertion (RPE) and session RPE (s-RPE). The results of linear mixed model analyses showed that TD ( d = 1.24–1.35), ACC ( d = 0.64–0.66), and DEC ( d = 0.90–1.04) were significantly higher on MD+1 in short microcycles compared to regular and long microcycles. On MD-4, large differences were observed between long and short microcycles for TD ( d = 1.60), ACC ( d = 1.28), DEC ( d = 1.28), RPE ( d = 1.25), and s-RPE ( d = 1.61). Similarly, MD-3 of long microcycles showed significantly higher TD ( d = 1.25–1.32), HIR ( d = 1.18–1.32), and SPD ( d = 0.84–1.68) compared to regular and short microcycles. On MD-2, the highest workload was observed in short microcycles, especially for SPD ( d = 1.15–1.34). Overall, this study demonstrated that the external and internal load of training sessions vary depending on the length of the microcycles in professional female soccer.